Ficolin-1 and Ficolin-3 Plasma Levels Are Altered in HIV and HIV/HCV Coinfected Patients From Southern Brazil - Tizzot, Maria Regina; Lidani, Kárita Cláudia Freitas; Andrade, Fabiana Antunes; Mendes, Hellen Weinschutz; Beltrame, Marcia Holsbach; Reiche, Edna; Thiel, Steffen; Jensenius, Jens C.; Messias-Reason, Iara J. de (Frontiers in Immunology, 2018)
The complement system is a key component of the innate immune system, participating in the surveillance against infectious agents. Once activated by one of the three different pathways, complement mediates cell lysis, opsonization, signalizes pathogens for phagocytosis and induces the adaptive immune response. The lectin pathway is constituted by several soluble and membrane bound proteins, called pattern recognition molecules (PRM), including mannose binding lectin (MBL), Ficolins-1, -2, and -3, and Collectin 11. These PRMs act on complement activation as recognition molecules of pathogen-associated molecular patterns (PAMPs) such as N-acetylated, found in glycoproteins of viral envelopes. In this study, Ficolin-1 and Ficolin-3 plasma levels were evaluated in 178 HIV patients (93 HIV; 85 HIV/HCV) and 85 controls from southern Brazil. Demographic and clinical-laboratory findings were obtained during medical interview and from medical records. All parameters were assessed by logistic regression, adjusted for age, ancestry, and sex. Significantly lower levels of Ficolin-1 were observed in HIV/HCV coinfected when compared to HIV patients (p = 0.005, median = 516 vs. 667 ng/ul, respectively) and to controls (p < 0.0001, 1186 ng/ul). Ficolin-1 levels were lower in males than in females among HIV patients (p = 0.03) and controls (p = 0.0003), but no association of Ficolin-1 levels with AIDS was observed. On the other hand, Ficolin-3 levels were significantly lower in controls when compared to HIV (p < 0.0001, medians 18,240 vs. 44,030 ng/ml, respectively) and HIV/HCV coinfected (p < 0.0001, 40,351 ng/ml) patients. There was no correlation between Ficolin-1 and Ficolin-3 levels and age, HIV viral load or opportunistic infections. However, Ficolin-3 showed a positive correlation with T CD4 cell counts in HIV monoinfected patients (p = 0.007). We provide here the first assessment of Ficolin-1 and−3 levels in HIV and HIV/HCV coinfected patients, which indicates a distinct role for these pattern recognition molecules in both viral infections.